Entoação e fonologia - Cagliari, Luiz Carlos [UNESP] (My University, 2012)
This paper is an outline of how intonation has been analyzed and described by phonologists and phoneticians within the framework of modern linguistics. Intonation is a prosodic reality that is concerned directly with the fundamental frequency in speech. Phonetically, intonation can be described physically with special equipments. But a phonological treatment of intonation data is a hard task for linguists. This paper presents part of this discussion.

Este artigo é uma apresentação geral de como a entoação tem sido analisada e descrita por fonólogos e por foneticistas, dentro da linguística moderna. A entoação é uma realidade prosódica relacionada diretamente com a frequência fundamental da fala. Foneticamente, a entoação pode ser descrita fisicamente com equipamentos especiais. Mas, um tratamento fonológico de dados entoacionais é uma tarefa difícil para os linguistas. Este artigo apresenta parte dessa discussão.
Intonation and phonology
Keywords: Intonation; Phonology; Entoação; Fonologia; Acústica da fala; Percepção auditiva fonética